2020
DOI: 10.1038/s41388-020-1325-1
|View full text |Cite
|
Sign up to set email alerts
|

Mdm4 supports DNA replication in a p53-independent fashion

Abstract: The Mdm4 (alias MdmX) oncoprotein, like its paralogue and interaction partner Mdm2, antagonizes the tumor suppressor p53. p53-independent roles of the Mdm proteins are emerging, and we have reported the ability of Mdm2 to modify chromatin and to support DNA replication by suppressing the formation of R-loops (DNA/RNA-hybrids). We show here that the depletion of Mdm4 in p53-deficient cells compromises DNA replication fork progression as well. Among various deletion mutants, only full-length Mdm4 was able to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Dot blots were conducted as described previously 24 . Cells were seeded, treated with Thap, BEPP or CHX as indicated and harvested.…”
Section: Dot Blot Analysismentioning
confidence: 99%
“…Dot blots were conducted as described previously 24 . Cells were seeded, treated with Thap, BEPP or CHX as indicated and harvested.…”
Section: Dot Blot Analysismentioning
confidence: 99%
“…It has also been demonstrated that silencing of SNRPD3 promoted MDM4 exon 6 skipping leading to the expression of a shorter and more labile transcript variant (Siebring-van Olst et al, 2017), which in turn could affect the level of MDM4 and p53-dependent and p53-independent functions of the protein (Haupt, Mejia-Hernandez, Vijayakumaran, Keam, & Haupt, 2019). For example MDM4 has recently been shown to facilitate unperturbed DNA replication via suppressing the formation of RNA-DNA hybrids (Wohlberedt et al, 2020). We observed substantially diminished Mdm4 mRNA levels in SHC016-expressing cells but only in those of murine origin (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation was carried out as described by our group [ 16 , 17 ] but modified as follows. The cells were cultivated while adherent on 145 mm dishes (Cat.…”
Section: Methodsmentioning
confidence: 99%